Understanding the etiology of adolescent substance use through developmental perspectives. (24th August 2021) - Trucco, Elisa M.; Hartmann, Sarah A.
Abstract: Using alcohol, cigarettes, and marijuana during adolescence is associated with risks, yet there is no single cause for adolescent substance use. The etiology of substance use develops over time, across multiple levels of influence. Informed by developmental perspectives, in this review, we provide an overview of biological (e.g., genetic, neuroimaging), individual (e.g., temperament, behavior problems), and social (e.g., parents, peers) factors that increase the risk for and protection against this multifaceted phenomenon. We also highlight emerging areas of research, as well as preliminary work examining the etiology of adolescent substance use across levels of influence. Understanding early factors associated with the emergence of adolescent substance use can help inform prevention programs to reduce subsequent cognitive impairments and psychopathology. Adaptive individualized interventions addressing various domains linked to adolescent substance use are likely to have significant utility given the numerous pathways to adolescent substance use.